Kinetic study of the sorption process with Cu(II) ions on clinoptilolite and analcime. Effects of temperature and particle size - CLAUDIA COBZARU; CRISTINA CIBOTARU; ADRIANA ROTARIU; ADRIANA MARINOIU; SPIRIDON OPREA (Chemical Industry and Chemical Engineering Quarterly, 2009)
The sorption process of the Cu(II) ions on the clinoptilolite and analcime containing volcanic tuff was studied at different temperatures like 40, 60 and 80 °C. The effects of temperature and a particle size on the sorption capacity of the used zeolites were analysed.